Convict criminology for the future - Ross, Jeffrey Ian; Vianello, Francesca Alice (Routledge, 2021)
"Bringing together a variety of diverse international contributors from the Convict Criminology community, Convict Criminology for the Future surveys the historical roots of Convict Criminology, the current challenges experienced by formerly incarcerated people, and future directions for the field. Over the past two decades research has been conducted in the field of Convict Criminology, recognizing that the convict voice has long been ignored or marginalized in academia, criminal justice practice, and public policy debates. This edited volume provides a much-needed update on the state of the field and how it has evolved. Seven primary themes are examined: Historical Underpinnings of Convict Criminology, Adaptations to prison life, Longstanding Challenges for Prisoners and Formerly Incarcerated People, Post Secondary Education behind bars, The expansion of Convict Criminology beyond North America, Conducting scholarly research in carceral settings Future Directions in Convict Criminology A global line up of contributors, from the fields of Criminology, Criminal Justice, Law, Political Science, and Sociology, comprehensively tackle each topic, reviewing causes, reactions, and solutions to challenges. The volume also includes a chronology of significant events in the history of Convict Criminology. Integrating current events with research using a variety of methods in scholarly analysis, Convict Criminology for the Future is invaluable reading for students and scholars of corrections, criminology, criminal justice, law, and sociology"--